凸轮机构恒流量往复泵动力端设计 - 董怀荣; 王平; 蔡文军; 张慧峰; 张吉平 (Jixie chuandong)
The special cam-drive mechanism is used as the power end of the new triplex single-function constant flow pump,which has been replaced for traditional crack-connecting rod mechanism.It results in which the motion law of piston is the complex motion law of same acceleration-same speed-same deceleration.The flow is constant and the pressure is not fluctuated.The design of power end of constant flow reciprocating pump with cam mechanism and analysis of flow characteristic are expounded in detail.